The growth hormone/insulin-like growth factor-1 axis in health and disease - LeRoith, Derek (Henry Stewart Talks, 2007)
Lack of growth hormone leads to short stature and excess leads to gigantism or acromegaly, IGF-1 is the main mediator of these effects, Both hormones have similar but different effects on protein, lipid and carbohydrate metabolism as well as bone development and growth, The IGF system plays a role in cancer progression
Reviewed at 2019/12/04